What explains positive social outcomes of community-based rangeland management in Mongolia? - Ulambayar, Tungalag, author; Fernandez-Gimenez, Maria, author; Batjav, Batbuyan, author; Baival, Batkhishig, author; Nutag Action and Research Institute, publisher (Colorado State University. Libraries, 2015)
Community-based rangeland management (CBRM) has been proposed as a promising option to reduce rural poverty and resource degradation in Mongolia. However, results have been mixed. Studies about the factors influencing CBRM success have been limited. We explored the mechanisms underlying social outcomes of Mongolian CBRM. The study revealed that access to diverse information, leadership, knowledge exchange and rules facilitated the effect of formal organization on pastoralists' traditional and innovative rangeland practices, proactive behavior, and social networking. Importantly, information diversity had a triggering effect on the other three facilitating variables. This chain of four mediators collectively increased the effect of the formal organization on the above social outcomes. We also found that ecological zone had a moderating effect on the relationship between formal organization and members' proactive behavior and social networking.
Presented at the Building resilience of Mongolian rangelands: a trans-disciplinary research conference held on June 9-10, 2015 in Ulaanbaatar, Mongolia.
Keywords: community-based management; pastoralism; Mongolia; social outcomes